INCREASING LEARNING OUTCOMES OF CHRISTIAN RELIGIOUS EDUCATION AND CHARACTERISTICS OF STUDENTS OF CLASS VIII SMP NEGERI 25 MEDAN THROUGH METHOD ROLE PLAYING 2018/2019 ACADEMIC YEAR - Sortauli Lumban Raja (Jurnal Scientia, 2022)
Improving Learning Outcomes of Christian Religious Education and Character for Class VIII Students of SMP Negeri 25 Medan Through the Role Playing Method for the 2018/2019 Academic Year. The method used in this research is the Classroom Action Research Method using 2 cycles, the subjects of this research are Class VIII students of SMP Negeri 25 Medan as many as 20 people, the instrument used to obtain data is by using tests, observing the range of values ​​for the test is Value highest and lowest . The instrument used for data processing is to calculate the number of students' scores who have not reached the KKM and the results of the y . score who have reached the KKM. The KKM has been determined, namely 70. The results of this study indicate that there is an increase in learning outcomes using the Role Playing Method with the following results: (1) In Cycle I, students get the highest score of 80, the lowest score of 25. Average score of 55.75 Then (2) in the second cycle increased to the highest value 95 The lowest value 80 , the average value is 86.5.